Flypaper Effect in PAD, DAU, & DAK on the Regional Expenditure in 2019-2023 - Ida Noviati Kusuma; Haryo Kuncoro Wiralaga; Puji Yuniarti (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
Fiscal decentralization is a tool to achieve maximum public welfare and the provision of essential public services. The essence of fiscal decentralization is the provision of transfer funds to local governments. In addition, through transfer funds, it is hoped that there will be equity and fiscal balance vertically and horizontally. However, the existence of transfer funds caused a response that the central government responded to as the main fund for regional spending. The purpose of this study is to determine the effect of the flypaper effect on the balance fund and local revenue on education spending, health spending, and infrastructure spending. Using data from 2019-2023 in municipalities and cities on the island of Java and regression using a fixed effect model, it shows the occurrence of a flypaper effect on education and infrastructure spending through DAK. As a result, every increase in DAK will encourage an increase in education and infrastructure spending. Meanwhile, different results are shown in health spending, that every increase in DAU decreases health spending. Different tests were carried out using dummy variables in the year before and after the implementation of the latest policy. As a result, the regulation of the DAU Specific Grant was able to increase health spending, but not as much as the influence of PAD.